Prevalent emm Types among Invasive GAS in Europe and North America since Year 2000 - Gherardi, Giovanni; Vitali, Luca Agostino; Creti, Roberta (Frontiers in Public Health, 2018)
Background: Streptococcus pyogenes or group A streptococcus (GAS) is an important human pathogen responsible for a broad range of infections, from uncomplicated to more severe and invasive diseases with high mortality and morbidity. Epidemiological surveillance has been crucial to detect changes in the geographical and temporal variation of the disease pattern; for this purpose the M protein gene (emm) gene typing is the most widely used genotyping method, with more than 200 emm types recognized. Molecular epidemiological data have been also used for the development of GAS M protein-based vaccines. Methods: The aim of this paper was to provide an updated scenario of the most prevalent GAS emm types responsible for invasive infections in developed countries as Europe and North America (US and Canada), from 1st January 2000 to 31st May 2017. The search, performed in PubMed by the combined use of the terms (“emm”) and (”invasive”) retrieved 264 articles, of which 38 articles, (31 from Europe and 7 from North America) met the inclusion criteria and were selected for this study. Additional 5 papers cited in the European articles but not retrieved by the search were included. Results: emm1 represented the dominant type in both Europe and North America, replaced by other emm types in only few occasions. The seven major emm types identified (emm1, emm28, emm89, emm3, emm12, emm4, and emm6) accounted for approximately 50-70% of the total isolates; less common emm types accounted for the remaining 30-50% of the cases. Most of the common emm types are included in either one or both the 26-valent and 30-valent vaccines, though some well-represented emm types found in Europe are not. Conclusion: This study provided a picture of the prevalent emm types among iGAS in Europe and North America since the year 2000 onwards. Continuous surveillance on the emm type distribution among iGAS infections is strongly encouraged also to determine the potential coverage of the developing multivalent vaccines.